2022
DOI: 10.1007/s11739-022-03164-w
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of long COVID-19 in people with previous SARS-Cov2 infection: a systematic review and meta-analysis of 120,970 patients

Abstract: The long-term consequences of the coronavirus disease 19 (COVID-19) are likely to be frequent but results hitherto are inconclusive. Therefore, we aimed to define the incidence of long-term COVID signs and symptoms as defined by the World Health Organization, using a systematic review and meta-analysis of observational studies. A systematic search in several databases was carried out up to 12 January 2022 for observational studies reporting the cumulative incidence of long COVID signs and symptoms divided acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 32 publications
2
37
1
Order By: Relevance
“…Other factors associated with longer-term symptoms that are identified in the literature, such as obesity, age, and female sex, were not associated with longer duration of symptoms when included in a multivariable model. A recent meta-analysis demonstrated that severity of COVID-19 (as measured by hospitalization) was not associated with risk of PCCs . In the EPICC study cohort, participants were at higher risk of reporting 28 or more days of symptoms if they were hospitalized during their initial infection or if they had higher self-reported symptom severity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other factors associated with longer-term symptoms that are identified in the literature, such as obesity, age, and female sex, were not associated with longer duration of symptoms when included in a multivariable model. A recent meta-analysis demonstrated that severity of COVID-19 (as measured by hospitalization) was not associated with risk of PCCs . In the EPICC study cohort, participants were at higher risk of reporting 28 or more days of symptoms if they were hospitalized during their initial infection or if they had higher self-reported symptom severity.…”
Section: Discussionmentioning
confidence: 98%
“…A recent meta-analysis demonstrated that severity of COVID-19 (as measured by hospitalization) was not associated with risk of PCCs. 26 In the EPICC study cohort, participants were at higher risk of reporting 28 or more days of symptoms if they were hospitalized during their initial infection or if they had higher self-reported symptom severity. Our findings may contribute to prognostic frameworks for advising those who may be more likely to develop PCCs.…”
Section: Jama Network Open | Infectious Diseasesmentioning
confidence: 99%
“…To the best of our knowledge, our study is the first to show the impact of low serum Mg status for long COVID and, in particular, for PTSD. Since long COVID may affect more than 50% of the patients previously hospitalized for COVID-19 [ 90 ], our study suggests the need to early identify and correct poor Mg status in order to help prevent this complication. Of importance, our study suggests that a peculiar association with psychiatric disorders may exist, confirming the previous literature in this direction [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, long COVID was detected using phone calls and not using other more validated tests, such as medical records. We have recently had the opportunity to review systematically and perform a meta-analysis of the incidence and frequency of signs and symptoms of long COVID according to the definition of the World Health Organization among 120,979 patients from 196 studies, as shown below [ 90 ]. In the [Supplementary Table S2 of the article, we report the characteristics of the 196 studies included, comprising the methods of follow-up assessing the symptomatology for the formulation of long COVID diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This question will need to be addressed in subsequent studies. A final limitation of our study is that we were unable to follow patients after discharge from hospital, to determine if they ultimately exhibited any post-acute sequelae of COVID-19 disease, i.e., signs or symptoms of “long COVID” [ 43 , 44 , 45 ]. It remains to be established whether SeptiCyte RAPID would have clinical utility in helping to diagnose this condition.…”
Section: Discussionmentioning
confidence: 99%